Beyond GDP : welfare across China and time. - Lin, Yumin. (2013)
This paper applies a comprehensive summary statistic of welfare measure for 336 prefectures in China, including Beijing, Chongqing, Shanghai and Tianjin. Shanghai is used as the benchmark prefecture city for prefectural comparison in the level results. The methodology employed by this paper is the extension of Charles I. Jones’s and Peter J. Klenow’s work: “Beyond GDP? Welfare across Countries and Time” on February 16, 2011. Similar to the reference paper, the approach in calculating the consumption-equivalent welfare, λ, is by using four variables: life expectancy, consumption, leisure and inequality. It therefore facilitates the systematic comparison of welfare with GDP per capita in the context of China’s prefectures in year 2005 and year 2010 as well as the growth rate across these two years. In general, this paper has found out that eastern prefectures represent higher welfare levels as compared to western prefectures but the latter had experienced higher growth rates during 2005 and 2010.